Factors affecting ESL students' willingness to communicate in English classroom discussions and their use of linguistic strategies - Jahedi, Maryam; Ismail, Lilliati (Horizon Research, 2020)
In the past few years, the importance of willingness to communicate (WTC) has received greater attention among scholars in the field as it has generally been found that WTC is closely related to the development of linguistic competence. This study employed the WTC Model (MacIntyre et al., 1998) and Halliday’s (1985) Systemic Functional Linguistics to examine Malaysian students’ WTC behavior through the analysis of classroom observations, journal entries and interview data. Thematic analysis was used to identify the situational factors affecting students’ WTC in classroom discussion interactions. Moreover, linguistic analysis of the data concentrated on interpersonal meaning of tenor to find out how students’ WTC was realized and how role relations were established among them through mood patterns and speech functions. The study found the major factors that increased the students’ WTC in the classroom discussions including topics of interest, relevance of the topic to one’s experience, teaching method, the relationship with peers, etc. Furthermore, the findings revealed that the students’ WTC was realized linguistically through the predominant use of declarative and interrogative discourse. Moreover, students tended to react more through supporting moves rather than confronting moves which showed a cooperative and positive atmosphere in the classroom. It can be concluded that students’ WTC in a particular situation is related to certain factors that promote their behavioral WTC to be manifested through language.